Epidemiology of diphyllobothriasis in the Valdivia River basin, Chile - Torres, Patricio; Franjola, René; Pérez, José; Auad, Sadi; Uherek, Fernando; Miranda, Juan C.; Flores, Luisa; Riquelme, Javier; Salazar, Samuel; Hermosilla, Claudia; Rojo, Rubén (Revista de Saúde Pública, 1989)
In the Valdivia (Chile) river basin 1,295 inhabitants of 6 riverside districts were examined between March and October 1987 and showed a 1.2% of prevalence by Diphyllobothrium in the districts of Riñihue and Las Huellas. Prevalence of 5.3% and 9.8% respectively were registered in dogs of the districts of Riñihue and Malihue. No cat or pig infection was observed in the different districts. The parasites recovered after the treatment were identified as Diphyllobothrium latum. Human infection by D. latum in the districts affected results from the consumption of smoked or insufficiently cooked fish. The investigation of 1,450 fish (4 exotic species and 11 autochthonous ones), caught in the Valdivia river basin in 1986 and 1987, showed the existence of plerocercoids of D. latum and/or Diphyllobothrium dendriticum in Salmo gairdneri and Salmo trutta among exotic fish and in some autochthonous species. Prevalence and mean intensity in the infection of fish as well as the degree of aggregation in the infrapopulations varied in the different districts. Some species of fish would act as intermediary hosts and others as paratenic hosts in the life cycles of Diphyllobothrium spp. in the Valdivia river basin. An improvement in the conditions of basic sanitation, in sanitary education and in the treatment of infected persons is proposed as a means for the control of diphyllobothriasis in the districts affected.